Road verges are refuges for small mammal populations in extensively managed Mediterranean landscapes - Ruiz-Capillas, Pablo; Mata, Cristina; Malo, Juan E (Biological Conservation, 2013)
Understanding how roads affect the persistence of animal populations is one of the challenges of road ecology. Small mammals are of great interest on account of their value as indicators of environmental impacts and their key role in ecosystems. Nevertheless, there is a large gap in our knowledge of small mammal communities in the proximity of roads. An intensive study was conducted of the effect of a motorway on the small mammal communities in an extensively managed Mediterranean landscape. Live-trapping methods were used over a 2-year period to characterise the structure and dynamics of small mammal populations at increasing distances from the motorway (0–500–1000 m). In total, 1004 individuals of three species were captured. All three were signiﬁcantly more abundant nearest to the motorway. In addition, in the case of the wood mouse, a higher proportion of juveniles was found at 0 m and 500 m from the motorway and its abundance was independent of other, habitat-related, characteristics. The greater abundance of small mammals in close vicinity to the motorway became more obvious during the second year, when a population crash reduced captures by over 60%. Thus, the ratio of captures alongside the motorway relative to those at the other distances analysed rose from approximately 3:2 to 9:2. The results point to roadside verges being an important refuge for small mammals in terms both of greater abundance and population stability. This ﬁnding has important implications from the viewpoint of conservation biology and for management of the environmental impacts of roads.
Keywords: Apodemus sylvaticus; Habitat degradation; microhabitat; Motorway; Population crash; rodents

Regeneration niche of the Canarian juniper: the role of adults, shrubs and environmental conditions - Otto, Rüdiger; Krüsi, Bertil O.; Delgado, Juan D.; Fernández-Palacios, José María; García-Del-Rey, Eduardo; Arévalo, José Ramón (Annals of Forest Science, 2010)
• Canarian Juniper woodlands, now very scarce, are rich in endemic and endangered plants. However, many aspects of juniper regeneration are almost unknown. • This paper relates occurrence and abundance of recruits of Juniperus turbinata ssp. canariensis to (1) small-scale soil characteristics; (2) vegetation cover; and (3) distance to conspeciﬁc adults in two contrasting juniper stands in the eastern mountains of Tenerife. We used non-parametric classiﬁcation trees and generalised linear models (GLM) to evaluate the eﬀect and importance of each explanatory variable on the occurrence of juniper saplings. • Sapling density, vitality and growth rate, as well as fruit production by adult trees, but neither cone density on the ground nor sapling size, varied signiﬁcantly with respect to slope orientation, representing environmental stress. Within each stand, distance to nearest adult tree was the most important variable explaining the spatial distribution of juniper saplings and availability of seeds in cones. Additionally, saplings were positively associated with shrub cover at the microsite-level, but not with spiny shrub cover. Soil depth and rock cover had a weak negative eﬀect on sapling establishment, but only at the south-facing site and in the open space microhabitat. • Results suggest that recruitment of Canarian juniper is facilitated by microhabitats oﬀered by adults and shrubs. The key factors aﬀecting recruitment are thought to be (1) favourable microenvironmental conditions and (2) high ambient seed availability. Browsing intensity in recent decades was very low. The presence of spiny shrubs did not favour juniper establishment. Facilitation therefore appears to result from amelioration of abiotic conditions rather than from protection against herbivory.
Keywords: Canary Islands; GLM; juniperus turbinata ssp canariensis; microhabitat; Regeneration